RETRACTED: Ecological groups of mammals found in Bukhara region and adjacent areas - Raimov A.R.; Bakayeva Sh.B.; Kalandarova D.S. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001